Penerapan Model UTAUT untuk Mengetahui Faktor-Faktor dalam Penerimaan dan Penggunaan Sistem Informasi Manajemen Pengawasan Daerah (SIMWASDA) - M Riyandra Alfariz Silaen; Dwi Rosa Indah; Mgs Afriyan Firdaus; Hardini Novianti (JURIKOM (Jurnal Riset Komputer), 2023)
The Regional Supervision Management Information System (SIMWASDA) is a web-based system with the function of documenting the oversight process performed by the Government Internal Supervisory Apparatus (APIP), especially the Inspectorate at the district, city, province and other levels when supervising all activities in the Regional Unit. Regional Apparatus Work. This Information System was also developed with the aim that each monitoring process becomes systematic and integrated. In general, SIMWASDA has not been implemented properly because system users have not utilized it optimally. Due to this, a study was conducted using the Unified Theory of Acceptance and Use of Technology (UTAUT) at the South Sumatra Provincial Inspectorate to identify factors that might have an impact on the acceptance and use of SIMWASDA. This study uses all variables from UTAUT along with 3 moderator variables. The number of respondents involved was 80 people. The results obtained show that social influence has the highest significant effect on the behavioral intention of SIMWASDA users and is followed by performance expectancy, while effort expectancy has an effect but not significant on the behavioral intention of SIMWASDA users. In addition, facilitating conditions and behavioral intentions have a significant influence on the use behavior of SIMWASDA users. In the moderating variable, age is a moderate variable that can weaken the effect of facilitating conditions on use behavior, but no moderation strengthens or weakens the effect on performance expectancy, effort expectancy or social influence of behavioral intention. There is no difference between gender which has a moderating effect in strengthening and weakening the influence on performance expectancy, effort expectancy and social influence on behavioral intention. After that, Experience completely has no moderating effect to strengthen or weaken the influence from effort expectancy, social influence and facilitating conditions of behavioral intention and use behavior. This study succeeded in accepting five hypotheses and rejecting ten hypotheses.